Spatio-temporal variation of reference evapotranspiration from empirical methods in Chihuahua, Mexico - Augusto Omar Villa-Camacho (Ingeniería agrícola y biosistemas, 2021)
Introduction: Evapotranspiration is key in the management of arid agricultural areas. In Chihuahua, the volume of irrigation water is based on reference evapotranspiration (ETo) calculated with empirical methods and extrapolated to the cropped area, which is inaccurate. The alternative is to calculate ETo variation by spatial interpolation.Objective: To analyze the spatio-temporal variation of ETo using empirical methods and spatial interpolation in Chihuahua, Mexico.Methodology: Records from 33 meteorological stations from 1960-2013 and seven ETo estimation methods were used. The results were compared with the Penman-Monteith method, modified by FAO (PMMF), ANOVA analysis (P ≤ 0.05), and homogeneous ETo surfaces built from the point values by spatial interpolation.Results: The Hargreaves method (R2 = 0.91, RMSE = 1.16 and ME = -0.69 mm-day-1) had a smaller bias with respect to PMMF. ETo values ranged from 2.5 to 7.1 mm-day-1 in a west-east direction, with maximum values at low elevations and minimum values at high elevations, which showed the influence of the Sierra Madre Occidental on ETo. This characteristic was most noticeable in the warm months (June to September).Limitations of the study: The use of estimated data needs field validation.Originality: The ETo estimation with seven empirical methods and one spatial interpolation method to extrapolate values to areas with scarce meteorological data.Conclusions: The Hargreaves method allows estimating the spatio-temporal variation of ETo in large extensions and areas with limited meteorological information.